Empty city spaces. Practices of unseen - Gańko, Anna (Journal of Education Culture and Society, 2019)
Aim. The aim of this paper is to depict ambivalent status of bygone city spaces - defined and identified by things that were there before - that are perceived as empty. Because they are obsolete, they do not function in accordance with their primarly intended use they become devastated and ruined, they create specific environment for various actions that in organised and sctructured spaces remain hidden and invisible.Method. The study is a reflexion on social functioning of city spaces perceived as abandoned – their ambivalent status in context of practices connected with urban space. Significant part of the article is a polemic with Kroessler's metaphore city as a palimpsest.Resullt and Conclusions. The analysis shows ambivalent status of urban spaces that are perceived as empty. They, by definition, consist of specific kind of absence and simoultaneously paradoxically they make some aspekts of urban space functioning visible.